Why the EU Still Matters in Turkish Domestic Politics: Insights from Recent Reforms in Migration Policy. Issue 1 (2nd January 2016) - Bürgin, Alexander
Abstract: In view of Turkey's increasing distance from the European Union (EU), the continued partial alignment with EU standards is often attributed either to domestic factors, or to diffusion processes induced by external actors other than the EU. However, based on interviews with officials from Turkey and the European Commission on recent reforms in migration policy, this article argues that two factors are responsible for continued EU influence on policy processes. First, the EU is still able to set incentives for compliance. Second, the instrument for pre-accession assistance has an impact that goes beyond that of a mere facilitator of domestically defined interests.